- Thread starter
- #1

- Jan 17, 2013

- 1,667

\(\displaystyle K(k)E'(k)+K'(k)E(k)-K(k)K'(k)=\frac{\pi}{2}\)

**Complete Elliptic integral of first kind**

\(\displaystyle K(k)= \int^1_0 \frac{dx}{\sqrt{1-x^2}\sqrt{1-k^2x^2}}\)

**Complete Elliptic integral of second kind**

\(\displaystyle E(k)= \int^1_0 \frac{\sqrt{1-x^2}}{\sqrt{1-k^2x^2}}dx\)

**Complementary integral**

\(\displaystyle K'(k)=K(k')=K\left(\sqrt{1-k^2} \right)\)

BONUS , prove that :

\(\displaystyle K(\sqrt{-1}\, k) = \frac{1}{\sqrt{1+k^2}} K\left(\frac{k}{\sqrt{1+k^2}}\right)\)

\(\displaystyle \frac{K'}{K}\left( \frac{1}{\sqrt{2}}\right)= 1 \, \)

\(\displaystyle \frac{K'}{K}\left( \frac{1}{\sqrt{2}}\right)= 1 \, \)

Last edited: